Employer's perception towards recruitment of physically challenged people and its effect on job opportunities - Ramachendran, Tenmoli (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to identify the perception of employers towards the recruitment ofphysically challenged people. Physically challenged people always face difficult times because they are always excluded from job opportunities. Their exclusion from employment, society and academic cause them to live below the breadline. Physically challenged people are frequently seen as burden by employers and employees. In this research, the study focuses about employer 's perception towards recruitment of physically challenged people and its effect on job opportunities. They are so many perceptions made. A few companies which hires and do not hires physically challenged people were chosen for the study. The study also focused on whether employers face problems when hiring and working with physically challenged people and how these does affects the job opportunities ofphysically challenged people. The findings ofthe study were supporting previous findings by past researches.